Permasalahan Pelanggaran Dan Langkah Hukum Hak Cipta Atas Musik Dan Lagu Yang Dituangkan Dalam Bentuk VCD Dan DVD - Budi Agus Riswandi (Fakultas Hukum Universitas Islam Indonesia, 2009)
The practice of trading music and songs which is set in the CD’s and DVD’s and also violate the copyrights on the Mataram Street Yogyakarta is mostly done. This of course invites problems in the context of copyright infringement and also a legal action to minimize it. Along the way, there has done a research related to it by using the method of empirical legal research. And the result are: there are a number of problems for copyright violations both in civil and criminal. Solution is giving the socialization about copyrights law and law enforcement.Key words : Copyright, problem, settlement